Pengetahuan Perawat Kamar Operasi tentang Keselamatan dan Kesehatan Kerja Sebagai Penentu Kepatuhan Terhadap Standard Operating Procedure Penggunaan Alat Pelindung Diri - Martzarini, Virginia; Yuswanto, Tri Johan Agus; Bachtiar, Arief (FORIKES, 2024)
Non-compliance with the use of personal protective equipment according to standard operating procedures by surgical nurses is often due to supervision factors, availability of equipment, and others. The operating room is a room that is at risk of threatening the health of officers, especially surgical nurses. This study aimed to determine the relationship between knowledge of hospital occupational safety and health and compliance with the implementation of standard operating procedures in the use of personal protective equipment by surgical nurses in the operating room. The research design used in this study was cross-sectional. The subjects of this study were 20 surgical nurses in the operating room in 2023, which were determined by the total sampling technique. Data on the level of knowledge were collected by filling out a questionnaire; while data on compliance with the use of personal protective equipment were collected through observation. Furthermore, data analysis was carried out using the Chi-square test. The results of the study showed that the p value of the correlation test was 0.001, so it was interpreted that there was a correlation between knowledge of hospital occupational safety and health and compliance with the implementation of standard operating procedures in the use of personal protective equipment by surgical nurses in the operating room. Furthermore, it was concluded that knowledge of occupational safety and health is a determinant of compliance with the implementation of standard operating procedures in the use of personal protective equipment by surgical nurses in the operating room.Keywords: occupational safety and health; operating room; nurse; knowledge; standard operating procedure; personal protective equipmentABSTRAK Ketidakpatuhan penggunaan alat pelindung diri sesuai standard operating procedure oleh perawat bedah sering dilakukan karena faktor pengawasan, ketersediaan alat, dan lain-lain. Kamar operasi adalah ruangan yang beresiko mengancam kesehatan petugas, khususnya perawat bedah. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan tentang keselamatan dan kesehatan kerja rumah sakit dengan kepatuhan pelaksanaan standard operating procedure dalam penggunaan alat pelindung diri oleh perawat bedah di kamar operasi. Desain penelitian yang digunakan dalam studi ini adalah cross-sectional. Subyek penelitian ini adalah 20 perawat bedah di kamar operasi pada tahun 2023, yang ditentukan dengan teknik total sampling. Data tentang tingkat pengetahuan dikumpulkan melalui pengisian kuesioner; sedangkan data tentang kepatuhan menggunakan alat pelindung diri dikumpulkan melalui observasi. Selanjutnya dilakukan analisis data menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa nilai p dari uji korelasi adalah 0,001, sehingga ditafsirkan bahwa ada korelasi antara antara pengetahuan tentang keselamatan dan kesehatan kerja rumah sakit dengan kepatuhan pelaksanaan standard operating procedure dalam penggunaan alat pelindung diri oleh perawat bedah di kamar operasi. Selanjutnya disimpulkan bahwa pengetahuan tentang keselamatan dan kesehatan kerja merupakan penentu kepatuhan pelaksanaan standard operating procedure dalam penggunaan alat pelindung diri oleh perawat bedah di kamar operasi.Kata kunci: keselamatan dan kesehatan kerja; kamar operasi; perawat; pengetahuan; standard operating procedure; alat pelindung diri